2011
DOI: 10.1093/nar/gkr376
|View full text |Cite
|
Sign up to set email alerts
|

Adenine and guanine recognition of stop codon is mediated by different N domain conformations of translation termination factor eRF1

Abstract: Positioning of release factor eRF1 toward adenines and the ribose-phosphate backbone of the UAAA stop signal in the ribosomal decoding site was studied using messenger RNA (mRNA) analogs containing stop signal UAA/UAAA and a photoactivatable cross-linker at definite locations. The human eRF1 peptides cross-linked to these analogs were identified. Cross-linkers on the adenines at the 2nd, 3rd or 4th position modified eRF1 near the conserved YxCxxxF loop (positions 125–131 in the N domain), but cross-linker at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 43 publications
8
31
0
Order By: Relevance
“…Based on nuclear magnetic resonance studies, it has been suggested that formation of a hydrogen bond between the carbonyl oxygen of S33 and the hydroxyl group of S70 in the UGA-only QFM_F mutant of human eRF1 stabilizes the GTS loop in conformation necessary for UGA recognition (46). These data are in agreement with cross-linking studies, indicating that although the GTS loop neighbours guanines of stop signals, it is positioned further from adenines (45). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Based on nuclear magnetic resonance studies, it has been suggested that formation of a hydrogen bond between the carbonyl oxygen of S33 and the hydroxyl group of S70 in the UGA-only QFM_F mutant of human eRF1 stabilizes the GTS loop in conformation necessary for UGA recognition (46). These data are in agreement with cross-linking studies, indicating that although the GTS loop neighbours guanines of stop signals, it is positioned further from adenines (45). …”
Section: Discussionsupporting
confidence: 90%
“…Mutagenesis based on the crystal structure of yeast eRF1•eRF3 complex with cocrystallized adenosine triphosphate (ATP) (which the authors suggest mimics a stop codon nucleotide) indicates a role for residue T32 in stop codon recognition (25). Cross-linking experiments also show that the GTx motif is proximal to the second and third guanine but more distal to the second and third adenine of stop codons, which may be compatible with alternate N-domain eRF1 conformations towards different stop codon bases within the ribosome (45).
Figure 1.Alignment of amino acid sequences of the N-terminal domains of human, yeast and Euplotes eRF1s.
…”
Section: Introductionmentioning
confidence: 99%
“…2). Binding of eRF1 under conditions used here is specific (i.e., occurs only if the A site is occupied with a stop codon [Bulygin et al 2002[Bulygin et al , 2010[Bulygin et al , 2011). Overall, complex 6 mimics a pretermination state, which takes place before GTP hydrolysis, whereas complex 7 corresponds to the post-termination state after GTP hydrolysis.…”
Section: Characterization Of the Ribosomal Termination Complexesmentioning
confidence: 99%
“…eRF1 is responsible for stop codon recognition and for triggering hydrolysis of the complex ester bond between the peptidyl moiety and the 3 ′ -terminal ribose of the peptidyl-tRNA located at the P site. Upon binding of eRF1 to ribosome, three highly conserved motifs of eRF1 (YxxCxxxF, TASNIKS, and GTS) located at the apex of the amino-terminal N domain mediate stop codon recognition (Bertram et al 2000;Song et al 2000;Chavatte et al 2002;Frolova et al 2002;Bulygin et al 2010Bulygin et al , 2011Conard et al 2012). Thereafter, the M domain of eRF1 binds to the peptidyl transferase center (PTC) of the ribosome inducing conformational rearrangement of the 28S rRNA and the subsequent release of the polypeptide chain (Frolova et al 1999;Song et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that loop 61-64 contains the conserved NIKS tetrapeptide sequence which is thought to be involved in the recognition of the first uridine of the stop codons 20,21 and the strictly conserved GTS loop sequence (position 31-33) which is implicated in the decoding of the stop codons. 18,20,28,29 The ability of human eRF1 to recognize each of the three stop codons UAA, UAG, and UGA and to distinguish them from the UGG tryptophan codon cannot be explained in terms of a simple static interaction. 30 It is obvious that the N-domain of human eRF1 should be able to undergo conformational rearrangements -not only in solution but also inside the ribosome.…”
Section: Discussionmentioning
confidence: 99%